Sources, transformation, and health implications of PAHs and their nitrated, hydroxylated, and oxygenated derivatives in PM2.5 in Beijing. Issue 14 (30th July 2015) - Lin, Yan; Ma, Yiqiu; Qiu, Xinghua; Li, Ran; Fang, Yanhua; Wang, Junxia; Zhu, Yifang; Hu, Di
Abstract Fine particulate matter (PM2.5) is a significant health issue in Chinese megacities. However, little information is available regarding the PM2.5‐bound toxic organics, especially their sources, atmospheric transformations, and health implications. In this study, we assessed the levels of polycyclic aromatic hydrocarbons (PAHs) and their nitrated, hydroxylated, and oxygenated derivatives (i.e., NPAHs, OHPAHs, and OPAHs, respectively) in PM2.5 collected in Beijing over a 1 year period. The median concentration of 23 PAHs, 15 NPAHs, 16 OHPAHs, and 7 OPAHs in PM2.5 was 53.8, 1.14, 1.40, and 3.62 ng m−3, respectively. Much higher concentrations and mass percentages for all species were observed in the heating season, indicating a higher toxicity of PM2.5 during this period of time. Positive matrix factorization was applied to apportion the sources of PAHs and their derivatives. It was found that traffic emissions in the nonheating season, and coal combustion and biomass burning in the heating season, were the major primary sources of PAHs and their derivatives. Secondary formation, however, contributed significantly to the derivatives of PAHs (especially NPAHs and OPAHs) in the nonheating season, suggesting significant impacts of atmospheric transformation on the toxicity of PM2.5.